Quality Degradation And Pricing of Perishable Food Products - Alastal, Haya (2024)
A Master of Science thesis in Engineering Systems Management by Haya Alastal entitled, “Quality Degradation and Pricing of Perishable Food Products”, submitted in December 2024. Thesis advisor is Dr. Malick Ndiaye. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).